2023
DOI: 10.1007/s10668-023-03298-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial intermediation through risk sharing vs non-risk sharing contracts, role of credit risk, and sustainable production: evidence from leading countries in Islamic finance

Abstract: The asset side of Islamic banks has two different portfolios running side by side, namely risk-sharing (PLS) and non-risk sharing (non-PLS) financing. The segregation of PLS and non-PLS financing has gathered some attention recently owning to its relative importance for sustainable economic output. This study attempts to analyze the impact of decomposed Islamic financing modes (PLS and non-PLS) with a particular focus on their impact on real economic activity. In addition, we moderated the relationship with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…Our study further captures the risk levels within companies, reported as a standard deviation of stock returns, with an average of 0.91 and a median of 0.85. The large standard deviation of 0.35 demonstrates that risk levels in the Saudi market vary significantly, a point also raised by [95]. Lastly, the average age of companies in our study, calculated from their date of establishment, is 1.44 with a median of 1.31.…”
Section: Conceptual Modelmentioning
confidence: 53%
“…Our study further captures the risk levels within companies, reported as a standard deviation of stock returns, with an average of 0.91 and a median of 0.85. The large standard deviation of 0.35 demonstrates that risk levels in the Saudi market vary significantly, a point also raised by [95]. Lastly, the average age of companies in our study, calculated from their date of establishment, is 1.44 with a median of 1.31.…”
Section: Conceptual Modelmentioning
confidence: 53%
“…This situation impacted the repayment capacity of borrowers, leading to an increase in non-performing financing levels (Rahmah & Armina, 2020)(Suzuki et al, 2020. The pandemic-related economic challenges have affected the financial performance of Islamic banks, emphasizing the need to address vulnerabilities in asset quality and operational efficiency to ensure financial stability (SISWANTORO, 2022) (Saleem, 2023)(Widarjono & Rudatin, 2021. Studies have explored the impact of financing diversification and the determinants of non-performing financing in Islamic banks, highlighting the importance of efficient operations and risk management practices ( (Lantara et al, 2022) (Mansour et al, 2021) (Ariani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Ijon system is more dominant due to cultural and social factors (Aswad, 2021;Latifa and Andriyani, 2022). Besides that, the future contract system also colors behavior in general, and the risk of bargaining position is low, but this can be anticipated by negotiating and utilizing financial/non-financial institutions (Algarvio, 2023;Saleem et al 2023). The implementation of the price of local soybeans at the farmer's level is IDR 8,000 per kg, and at the district collector's level, is IDR 12,000/kg.…”
Section: Introductionmentioning
confidence: 99%